Hukum Islam: Antara Statis dan Dinamis - Bambang Prawiro, Abdurrahman Misno (UIN Sunan Kalijaga, 2014)
Globalization era brought mankind to the complex life whereas Islam was completed by the ending of revelation period. Human being with their complex problem need a system of law that be able to be a problem solving for every problem. However, a dinamic and flexible system of law that be able to exist in the dynamic human life. So what about islamic law system? can it respond every problem had by mankind? Or will it be a historical evident as a kind of human civilization? Islamic law is a method of life coming from God, therefore, since turning down revelation it will and must uptodate in every time and place. Yet, how can Islam adapt to the social development? This writing discusses the flexible and dynamic dimension of islamic law.